The Relatedness between Hepatitis B Virus from Non-Papuan Blood Donors in Jayapura and the Papuan Clusters - VICTOR EKA NUGRAHAPUTRA; MOCHAMAD AMIN; NI MADE MERTANIASIH; MARIA INGE LUSIDA (Microbiology Indonesia, 2009)
The genotypes (A-H) and subtypes (adw2, adw4, adrq-, adrq+, ayw1-4, ayr) of HBV show distinct geographical distributions, which have been associated with anthropological history. The novel finding of the HBV subgenotypes C6 and D6 from Papuans formed a specific cluster distinct from the previous HBV subgenotypes C1-C5 and D1-D5. In this study we determined the most recent genotype-subtype patterns of the HBV from non-Papuan blood donors who live in Jayapura and their phylogenetic relatedness, especially with the Papuan clusters. Fifteen HBsAg-positive serums were obtained from non-Papuan blood donors including from people in Java (46.7%), Maluku (26.7%), Sulawesi (20%) and East Nusa Tenggara (6.7%). S gene of all HBV serum isolates were partially sequenced and analyzed. Most HBV isolates (53.3%) were classified as genotype B, followed by genotype C(26.7%) and D (20.0%). The subtype adw2 (33.3%) was predominant, followed by adrq+ (26.7%) and ayw1/ayw2 (20.0%). All HBV isolates with subtype adw2 and ayw1 belonged to genotype B, while adrq+ belonged to genotype C and ayw2 belonged to genotype D. The most predominant HBV genotype-subtype (B/adw2) was consistent with the ethnic background (mostly from Java people). Nevertheless, based on the phylogenetic relatedness, many non Papuan isolates (40%) were classified into HBV/C6 and HBV/D6 of the Papuan clusters. Other isolates were classified into HBV/C1, HBV/B3 and HBV/B7. In conclusion, many HBV isolates from non-Papuans in Jayapura belonged to the Papuan clusters, but others had different genotype-subtype patterns with frequencies dependent on ethnicity.